ANALISA PENGGUNAAN PROVIDER PERANGKAT MI-FI TERHADAP PERFORMA GAME MOBILE LEGENDS BANG BANG MODE RANKED - Maulana Ridho Alfarizqa; Made Sutha Yadnya; Abdullah Zainuddin (Postgraduate, University of Mataram, 2025)
Online games are a worldwide achievement supported by technological advances that want the best for smartphone users. A weakness or failure in wireless communication is the propagation of the path used. Service providers or provaider have advantages and disadvantages. One of the things that makes it different is the weather conditions, normal weather conditions and rain. Special measurements in Ranked mode, which are carried out in the championship as a single target in order to be the winner, the stability of the connection is crucial to ensure that players can play without any network connection interruptions. This paper contributes to revealing the online game process by analyzing the performance performance of three internet providers (Telkomsel, XL, and Tri) in playing Mobile Legends: Bang Bang, especially in Ranked mode. Measurement using Mi-Fi with postpaid access (no quota restrictions) as an assumption of the same conditions for each provaider. Measurements are carried out using key parameters such as throughput, packet loss, and delay so that the results of the analysis are obtained using statistical methods to search for averages and variances. The results of the analysis from the calculation were obtained that Telkomsel outperformed XL and Tri.